Warm Acupuncture Reduces Pain and Inflammation in Rats with Lumbar Disc Herniation Induced by Autologous Nucleus Pulposus Transplantation via Regulating p38MAPK/NF-κB Pathway - Feng Pan; Feng Zeng; Yanbei Chen; Yongren Zheng; Zhihong Chen; Xiaoju Zhu; Mei Fang Yin; Yiran Huang; Zheng Liu (Medical Association of Pharmacopuncture Institute, 2024)
Background : Warm acupuncture (WA) has analgesic and anti-inflammatory effects. However, the underlying mechanism of these effects remain unclear. Objectives: To explore the analgesic and anti-inflammatory effects of WA and the potential underlying mechanism in male Sprague-Dawley rats with non-compressive lumbar disk herniation (LDH) caused by autologous nucleus pulposus (NP) transplantation. Methods : We used low-frequency (2 Hz) electrical stimulation and WA (40℃) to treat GB30 and BL54 acupoints in rats for 30 mins per day. We monitored the paw withdrawal threshold of rats during the experiment and measured serum cytokine levels using commercial kits. Dorsal root ganglion (DRG) tissue pathology was analyzed via H&E staining. We used qRT-PCR to measure the mRNA expression levels of IL-1β, IL-6, and TNF-α genes in DRG. Western blot was used to analyze the expression levels of IL-1β, IL-6, TNFα, P-p38MAPK, p38MAPK, P-IκBα, IκB α, and NF-κB p65 proteins. Results : WA treatment significantly increased the pain threshold of rats, reduced serum IL-6, PEG2, NO, SP, NP-Y, and MMP-3 levels, and effected histopathological improvements in the DRG in rats. Moreover, WA treatment significantly downregulated the expression levels of inflammation-associated genes (Il-1β, Il-6, and Tnf-α) and proteins (IL-1β, IL-6, TNF-α, P-p38MAPK, P-IκBα, and NF-κB p65) in the DRG of non-compressive LDH rats. Conclusion : WA can alleviate pain and inhibit inflammatory response in rats with non-compressive LDH caused by autologous NP transplantation, and these effects are likely associated with the inhibition of the p38MAPK/NF-κB pathway.